Pengaruh Pemberian Limbah kulit Kopi dan Perendaman Air Bawang Merah terhadap Pertumbuhan Stek Kumis Kucing (Orthosiphon aristatus) - Dwi Sekar Ningtias; Desi Sri Pasca Sari Sembiring; Najla Lubis (Jurnal Riset Rumpun Ilmu Tanaman, 2026)
This study aimed to determine the effect of coffee husk waste application and shallot extract soaking on the growth of cat’s whiskers (Orthosiphon aristatus) cuttings. The research employed a factorial Randomized Block Design (RBD) consisting of two factors with 48 experimental plots. The first factor was the application of coffee husk waste, symbolized as “L,” with four treatment levels: L0 = 0 g/polybag (without coffee husk waste), L1 = 75 g/polybag, L2 = 150 g/polybag, and L3 = 225 g/polybag. The second factor was shallot extract soaking, symbolized as “B,” with four treatment levels: B0 = 0 ml/L of water, B1 = 5 ml/L of water, B2 = 10 ml/L of water, and B3 = 15 ml/L of water. Thus, there were 16 treatment combinations with three replications. The observed parameters included time to shoot emergence, number of shoots, plant height, number of leaves, leaf area, and survival percentage. The results showed that the application of coffee husk waste and shallot extract soaking had no significant effect on the growth of cat’s whiskers (Orthosiphon aristatus) cuttings across all observed parameters.